A novel indomethacin/methotrexate/MMP-9 siRNA in situ hydrogel with dual effects of anti-inflammatory activity and reversal of cartilage disruption for the synergistic treatment of rheumatoid arthritis. Issue 15 (3rd April 2020) - Yin, Na; Tan, Xinyi; Liu, Hongbing; He, Fengming; Ding, Ning; Gou, Jingxin; Yin, Tian; He, Haibing; Zhang, Yu; Tang, Xing
Abstract : The D/siRNA-NGel was constructed to alleviate pain and swelling, delay the progression of RA, and reverse cartilage and bone disruption. Abstract : Rheumatoid arthritis (RA) is an autoimmune disease characterized by inflammatory cell infiltration, and cartilage and bone disruption, which ultimately leads to loss of joint function. Current treatments for RA only focus on anti-inflammatory activity but neglect to prevent further damage to articular cartilage and bone. Here we attempted to co-deliver indomethacin (IND), methotrexate (MTX) and a small-interfering RNA targeting MMP-9 using an in situ hydrogel loaded with PEI-SS-IND-MTX-MMP-9 siRNA nanoparticles (D/siRNA-NGel) to treat RA synergistically and comprehensively. IND, MTX and MMP-9 siRNA were able to escape from the endosome and down-regulate the expression of MMP-9 and inflammatory cytokines of Raw-264.7 cells. After intra-articular injection in arthritic mice, the D/siRNA-NGel effectively relieved joint swelling and significantly reduced the expression of TNF-α, IL-6 and MMP-9 in the ankle fluid, knee joint fluid and plasma of RA mice without causing any side effects. Most importantly, the co-delivery system restored the morphological parameters of the ankle joints close to normal. The D/siRNA-NGel could achieve good anti-inflammatory activity and reverse cartilage disruption through a synergistic effect between chemical drugs and MMP-9 siRNA. This co-delivery system should have promising applications in the treatment of rheumatoid arthritis and other metabolic bone diseases which cause serious bone erosion.